2014
DOI: 10.1021/jp412281n
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Anions in Organic Ionic Compounds. An ab Initio Study of Selected Ion Pairs

Abstract: The combination of amino acids in their deprotonated and thus anionic form with a choline cation gives origin to a new and potentially important class of organic ionic compounds. A series of such neutral ion pairs has been investigated by first principle methods. The results reveal intriguing structural motives as well as regular patterns in the charge distribution and predict a number of vibrational and optical properties that could guide the experimental investigation of these compounds. The replacement of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
75
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 70 publications
6
75
1
Order By: Relevance
“…Maginn and co-workers did not observe inter-leaflet diffusion of [bmim][Cl] in POPC, and S.K. Wiedmer and co-workers did observe inter-leaflet diffusion of different RTILs in POPC, we can conclude that the disagreement is due to the important role played by the RTIL chemistry, in line with our neutron reflectivity results (Benedetto et al 2014b). …”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…Maginn and co-workers did not observe inter-leaflet diffusion of [bmim][Cl] in POPC, and S.K. Wiedmer and co-workers did observe inter-leaflet diffusion of different RTILs in POPC, we can conclude that the disagreement is due to the important role played by the RTIL chemistry, in line with our neutron reflectivity results (Benedetto et al 2014b). …”
Section: Introductionsupporting
confidence: 89%
“…This article is part of a Special Issue on 'IUPAB Edinburgh Congress' edited by Damien Hall (v) Penetrate, create pores, and destroy biomembranes (Benedetto et al 2014b, Bhattacharya et al 2017, Evans 2008, Yoo et al 2014, b, Wang et al 2015a, b, 2016Drücker et al 2017; and (vi) Dissolve cellulose and other complex polysaccharides (Youngs et al 2011, Zhang et al 2017, Cheng et al 2011, Liu et al 2010.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23][24][25] On the theoretical front, molecular dynamics (MD) simulations on the ILs composed of deprotonated amino acid anions and choline cation revealed that their formation is facilitated through proton transfer involving the hydrogen bond effectively neutralizing cation and anion. 26 Fileti and coworkers 27 A molecular level understanding of noncovalent interactions encompassing hydrogen bonding, steric repulsion, aromatic ring stacking and electrostatic interactions should prove useful 5 for designing of task specific ILs. To this direction interactions arising from aromatic rings or π-stacking have received significant attention in the recent years.…”
Section: Introductionmentioning
confidence: 99%